Modeling the shape of cylindrically focused transducers in three-dimensional optoacoustic tomography - Queiros, Daniel; Dean-Ben, Xose Luis; Buehler, Andreas; Razansky, Daniel; Rosenthal, Amir; Ntziachristos, Vasilis (Journal of Biomedical Optics, 2013)
Cross sectional tomographic systems based on cylindrically focused transducers are widely used in optoacoustic (photoacoustic) imaging due to important advantages they provide such as high-cross sectional resolution, real-time imaging capacity, and high-throughput performance. Tomographic images in such systems are commonly obtained by means of two-dimensional (2-D) reconstruction procedures assuming point-like detectors, and volumetric (whole-body) imaging is performed by superimposing the cross sectional images for different positions along the scanning direction. Such reconstruction strategy generally leads to in-plane and out-of-plane artifacts as well as significant quantification errors. Herein, we introduce two equivalent full three-dimensional (3-D) models capable of accounting for the shape of cylindrically focused transducers. The performance of these models in 3-D reconstructions considering several scanning positions is analyzed in this work. Improvements of the results rendered with the introduced reconstruction procedure as compared with the 2-D-based approach are described and discussed for simulations and experiments with phantoms and biological tissues. © 2013 Society of Photo-Optical Instrumentation Engineers.
CRIS-Team Scopus Importer:2023-03-08
Keywords: focused transducer; image reconstruction; optoacoustic tomography; photoacoustic tomography